Levels of neuroinflammation markers in type 2 diabetes mellitus patients with diabetic retinopathy and genetically determined hyperhomocysteinemia - Iu. O. Panchenko; V. S. Tsybulskyi; L. V. Natrus; H. Ie. Zakharevych (Ukrainian Society of Ophthalmologists, 2024)
Background: Hyperhomocysteinemia determined by polymorphisms of genes encoding folate cycle enzymes is closely correlated with markers of systemic inflammation. Prolonged excessive cytokine production in the neural tissue in patients with type 2 diabetes mellitus (T2DM) causes gliosis, posing a threat of neuroinflammation, a potential pathogenetic component of diabetic retinopathy (DR). Purpose: To assess plasma levels of neuroinflammation markers (IL-1β and IL-10) and gliosis marker, non-neuronal enolase (NNE), in T2DM patients with DR and genetically determined hyperhomocysteinemia. Methods: One hundred and six T2DM patients with DR were involved in the study. DR severity was classified according to ETDRS DR severity system (DRSS) as non-proliferatve (NPDR; DRSS level 47-53), proliferative (NPDR; DRSS level 47-53) and advanced (APDR; DRSS level 81-85). The control group was composed of 64 individuals. Cases and controls were comparable for age, sex and way of life. MTHFR C677T (rs1801133), MTHFR A1298C (rs1801131), and MTR A2756G (rs1805087) genotypes were determined using the TaqMan® SNP Genotyping Assay (Applied Biosystems, Foster City, CA) and the ABI 7500 real-time PCR system (Applied Biosystem). Enzyme-linked immunosorbent assay (ELISA) kits were used to assess plasma levels of L-homocystein, cytokines and NNE. Results: Plasma IL-1β levels were 1.7 times higher in patients with diabetes duration shorter than 15 years compared to those with longer diabetes duration. In addition, plasma NNE levels were higher in the former patients, but the difference was not significant. There was correlation of plasma L-homocystein levels with plasma IL-10 (R = 0.357, p < 0.01), IL-1b (R = 0.320, p < 0.01) and NNE (R = 0.286, p < 0.01) levels. Plasma NNE levels correlated with plasma IL-10 (R = 0.279, p < 0.01) and IL-1beta (R = 0.368, p < 0.01). Conclusion: Elevated plasma levels of pro-inflammatory cytokines in patients indicate an important role of neuroinflammation in the pathogenesis of DR. The rs1801131 CC, rs1805087 GG and rs1801131 CC genotypes may be considered risk factors for the development of DR in patients with T2DM.